2008
DOI: 10.1016/j.placenta.2008.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Placental System A Amino Acid Transport is Reduced in Pregnancies With Small For Gestational Age (SGA) Infants but Not in Preeclampsia with SGA Infants

Abstract: Preeclampsia and intrauterine growth restriction (IUGR) are both associated with abnormal remodeling of maternal spiral arteries perfusing the placental site. This would be expected to be associated with reduced fetal growth, yet only one third of infants of mothers with preeclampsia are growth restricted. Infants with IUGR have decreased concentrations of amino acids in their blood and system A amino acid transporter activity is reduced in their placentas. Since infants of preeclamptic pregnancies have increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 23 publications
4
56
0
Order By: Relevance
“…We propose that these mechanisms seen in other tissues may also be present in the placenta. Consistent with this, we have found that in placentas from SGA infants from mothers without PE in which adenosine receptors were not increased in our studies there was reduced uptake by system A amino acid transport in vitro [41]. However, in placentas from PE pregnancies with SGA infants in which adenosine receptors are increased, system A uptake was normal [41].…”
Section: Discussionsupporting
confidence: 87%
“…We propose that these mechanisms seen in other tissues may also be present in the placenta. Consistent with this, we have found that in placentas from SGA infants from mothers without PE in which adenosine receptors were not increased in our studies there was reduced uptake by system A amino acid transport in vitro [41]. However, in placentas from PE pregnancies with SGA infants in which adenosine receptors are increased, system A uptake was normal [41].…”
Section: Discussionsupporting
confidence: 87%
“…Conversely, FGR without pre-eclampsia occurs as a result of the absence of this signal. 38,40 We suggest that this model could be applied to the FGR cases of this study. Based on our results, it can be hypothesised that FGR babies with less severe disease produce a signal stimulated by the reduced placental nutrient and oxygen availability, in contrast to FGR babies with a more adverse outcome that fail to produce this signal.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the uptake of C 14 -MeAIB, a specific substrate transported by system A, was measured in sodium-containing and sodium-free (for non-specific uptake) Tyrodes buffer containing C 14 -MeAIB (1.7 μmol/L, 0.05μCi/ml) for 40 min at 37°C. Previous studies showed that the uptake of C 14 -MeAIB is linear up to 180 min [31, 32]. The uptake of C 14 -MeAIB by villous fragments was stopped by washing the fragments in ice-cold sodium-free Tyrodes buffer two times for 20 sec each.…”
Section: Methodsmentioning
confidence: 99%